Exercise under hot conditions: a major threat to the immune response? - Shephard, R. J. (The Journal of Sports Medicine and Physical Fitness, 2002)
It seems likely that the disturbances of immune response induced by prolonged competitive exercise are exacerbated if athletes also face the stress of hot environmental conditions. We have investigated this question by manipulating the exercise-induced increases of body temperature in a climatic chamber and by submersion of exercisers in a large water-bath. Hot conditions increase the stress of a given bout of exercise, as assessed by personal perceptions, objective (heart rate variability) measures of autonomic nerve balance, and the secretion of "stress" hormones, with a parallel increase in effects upon critical lymphocyte subsets. Changes in the immune response show substantial correlations with plasma concentrations not only of epinephrine (which modulates the adhesiveness of peripherally sequestered lymphocytes), but also with norepinephrine. The latter hormone may mobilize leukocytes from the spleen and lymph glands, or it may act by increasing cardiac output and thus intravascular shear forces. Given the cumulative impact of various environmental stressors upon the immune system, every effort should be made to minimize the athlete's exposure to stresses other than the exercise to be performed. In some circumstances, the use of medications to reduce the overall stress response may also be warranted.